IMPLEMENTATION OF NUMBERED HEAD TOGETHER STRATEGY IN SETTING STAD MODEL LEARNING - Muhammad Mifta Fausan (University of Muhammadiyah Malang, 2016)
This study aims to determine the increase of motivation and biology student learning outcomes through the implementation of Numbered Head Together (NHT) strategies in setting Student Teams Achievement Division (STAD) learning model based Lesson Study (LS). Subjects in this study were students of class X IS 1 MAN 3 Malang. Implementation this study consisted of two cycles and each cycle consisted of three meetings. The data obtained were analyzed using descriptive statistical analysis of qualitative and quantitative descriptive statistics. The research instrument used is the observation sheet, test, monitoring LS sheets and questionnaires. The results of this study indicate that through the implementation of NHT strategy in setting STAD learning model based LS can improve motivation and learning outcomes biology students. Students' motivation in the first cycle of 69% and increased in the second cycle of 86%. While the cognitive learning, classical completeness in the first cycle of 74% and increased in the second cycle to 93%. Affective learning outcomes of students in the first cycle by 93% and increased in the second cycle to 100%. Furthermore, psychomotor learning outcomes of students also increased from 74% in the first cycle to 93% in the second cycle. Keywords: Biology Learning Outcomes, Lesson Study, Motivation, Numbered Head Together, Student Teams Achivement Division.